Using An Electrical Toothache Salvadora Perisca To Increasing Oral Health Quality: A Manikin Trial - Satino Satino; Yuyun Setyorini; Rendi Editya Darmawan ((JKG) Jurnal Keperawatan Global, 2022)
Background: The most effective way of oral care in patients with decreased consciousness is not yet known. Electrical toothace salvadora perisca has the potential to improve oral hygiene because it has an antibiotic effect, and is easy to use. Aim of study is to know the effect of electrical toothace salvadora perisca on oral health quality. Methods: A pre-experimental study in a laboratory using manikins in 2021. The study was conducted by 6 respondents in which each respondent performed 2 oral treatments using an electrical toothace salvadora perisca on the mouth of a manikin that had been dirty make-up using Ky Jelly. The toothbrush was operated for 1 minute evenly on the teeth, and foam sticks are used to clean the lips and oral mucosa. Oral hygiene was measured with a modified Beck Oral Assessment Scale (BOAS) instrument, and the scores of conditions before and after oral care were compared using the Wilcoxon test. Results: Wilcoxon test showed a value of 0.002, which means that there was a difference in the BOAS score between before and after treatment. Electric toothbrushes clean teeth better, and foam sticks are able to clean the inside and soft of the patient's mouth. Conclusion: Electrical toothace salvadora perisca can increasing oral health quality. The implication is need to find and try out the most effective way of doing oral care.